A Strong form of Cl-Cl -Connectedness (International Journal of Scientific Research and Management (IJSRM), 2017)
• Modak and T. Noiri introduced a weak form of connectedness[1] in topological space called - -connectedness. In this paper, we introduce the notion of - -separated sets and - -connectedness spaces which is strong form of - -connectedness. We obtain several properties of this notion.